Correction: Silva et al. Multiple Dimensions of Energy Efficiency of Recycled Concrete: A Systematic Review. Energies 2024, 17, 3809 - Leandro S. Silva; Mohammad K. Najjar; Carina M. Stolz; Assed N. Haddad; Mayara Amario; Dieter Thomas Boer (Energies, 2025)
There was an error in the original publication [...]